2011
DOI: 10.4067/s0718-58392011000300019
|View full text |Cite
|
Sign up to set email alerts
|

Residual Glycerol from Biodiesel Manufacturing, Waste or Potential Source of Bioenergy: A Review

Abstract: This review provides a summary of the research conducted on the use of crude glycerol, the major byproduct of the biodiesel industry, as substrate for anaerobic co-digestion and production of biogas. In general, for every 100 kg biodiesel produced, approximately 10 kg crude glycerol is generated. Because this glycerol is expensive to purify for use in food, pharmaceutical, or cosmetic industries, biodiesel producers must seek alternative methods for its disposal. Several studies have demonstrated that the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 39 publications
0
49
0
5
Order By: Relevance
“…It was found that for initial concentration of 70 g/L crude glycerol, certain impurities inhibited the cell growth. Soap and methanol have been found to negatively influence the algae production of DHA from crude glycerol [60] and the high salinity (Na or K) of crude glycerol can largely inhibit the microbial activity in the anaerobic digestion of crude glycerol [61]. Studies also show that saponified fatty acids (SFA) have inhibitory effect on photofermentative growth of Rhodopseudomonas palustris on crude glycerol to produce hydrogen [12].…”
Section: Effect Of Impurities On Glycerol Utilizationmentioning
confidence: 98%
“…It was found that for initial concentration of 70 g/L crude glycerol, certain impurities inhibited the cell growth. Soap and methanol have been found to negatively influence the algae production of DHA from crude glycerol [60] and the high salinity (Na or K) of crude glycerol can largely inhibit the microbial activity in the anaerobic digestion of crude glycerol [61]. Studies also show that saponified fatty acids (SFA) have inhibitory effect on photofermentative growth of Rhodopseudomonas palustris on crude glycerol to produce hydrogen [12].…”
Section: Effect Of Impurities On Glycerol Utilizationmentioning
confidence: 98%
“…However, glycerin obtained from the process of production and the obtainment of esters (approximately 10 kg of glycerin are generated for every 100 L of biodiesel produced) has several impurities such as water, fatty waste, catalyst residues and a high chemical oxygen demand (Santibañez, Varnero, & Bustamante, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, liquid waste generated during fermentative hydrogen production using pure/crude glycerol could be considered as a potential renewable source of PD. Crude glycerol is a byproduct of biodiesel manufacturing by trans-esterification process and nearly 10 kg of crude glycerol is generated for every 100 kg of biodiesel produced [35]. Although it is an expensive process [35]; glycerol can be recovered from crude glycerol [36].…”
Section: 3-propanediol Recovery From Hplwmentioning
confidence: 99%